Erosi Tanah Akibat Operasi Pemanenan Hutan (Soil Erosion Caused by Forest Harvesting Operations) - Ujang Suwarna; Harnios Arief; Mohammad Ramadhon (Jurnal Manajemen Hutan Tropika, 2009)
Forest harvesting operation has been known as an activity that should be considered as the main cause of soil erosion. Indonesia, the second largest owner of tropical forest, should have a serious consideration to the operation.  Therefore, the study was conducted in logged over area of a natural production forest.  The objectives of the study was to examine level of soil erosion caused by forest harvesting operations and to analyze a strategy to control level of the erosion based on its influencing factors. The study showed that forest harvesting operations caused soil erosion.  Factors that influenced the high level of the erosion were high level of precipitation, lack on planning of forest harvesting operations, no applying treatment of cross drain and cover crop in the new skidding roads, no culture of carefulness in the operations, and low human resource capacity in applying environmentally friendly forest harvesting techniques. Keywords: soil erosion, forest harvesting, logged over area, skidding road